Book review: P. Neethi and Anant Kamath, Urban Undesirables: City Transition and Street-Based Sex Work in Bangalore. (June 2023) - Shivanand, Swathi
P. Neethi and Anant Kamath, Urban Undesirables: City Transition and Street-Based Sex Work in Bangalore, Cambridge University Press, 2022, 240 pp., ₹895, ISBN 978-1009180214 (Hardcover).